Pressure overload-induced systolic heart failure is associated with characteristic myocardial microRNA expression signature and post-transcriptional gene regulation in male rats - Ruppert, Mihály; Korkmaz-İçöz, Sevil; Benczik, Bettina; Ágg, Bence; Nagy, Dávid; Bálint, Tímea; Sayour, Alex Ali; Oláh, Attila; Barta, Bálint András; Benke, Kálmán; Ferdinandy, Péter; Karck, Matthias; et al. (Scientific reports, 2023)
Although systolic function characteristically shows gradual impairment in pressure overload (PO)-evoked left ventricular (LV) hypertrophy (LVH), rapid progression to congestive heart failure (HF) occurs in distinct cases. The molecular mechanisms for the differences in maladaptation are unknown. Here, we examined microRNA (miRNA) expression and miRNA-driven posttranscriptional gene regulation in the two forms of PO-induced LVH (with/without systolic HF). PO was induced by aortic banding (AB) in male Sprague-Dawley rats. Sham-operated animals were controls. The majority of AB animals demonstrated concentric LVH and slightly decreased systolic function (termed as ABLVH). In contrast, in some AB rats severely reduced ejection fraction, LV dilatation and increased lung weight-to-tibial length ratio was noted (referred to as ABHF). Global LV miRNA sequencing revealed fifty differentially regulated miRNAs in ABHF compared to ABLVH. Network theoretical miRNA-target analysis predicted more than three thousand genes with miRNA-driven dysregulation between the two groups. Seventeen genes with high node strength value were selected for target validation, of which five (Fmr1, Zfpm2, Wasl, Ets1, Atg16l1) showed decreased mRNA expression in ABHF by PCR. PO-evoked systolic HF is associated with unique miRNA alterations, which negatively regulate the mRNA expression of Fmr1, Zfmp2, Wasl, Ets1 and Atg16l1.
Online publiziert: 26. September 2023
Gesehen am 06.02.2024